A oferta de educação no sistema prisional no Tocantins - Coimbra, Valdir Santos Rodrigues (2018)
This research investigates the education offer in the prison system in Tocantins. Thus, its main objective is to investigate the space occupied by education in the prison system in Tocantins and specially in Araguaína city. Through the main objective, it was possible (a) to investigate the origins of prison education in Brazil (historical trajectory); (b) to identify in the oficial documents the federal, state and municipal levels the legal prerogatives and the objectives and guidelines of prison education; (c) to relate the objetives and functioning mechanisms of prison education in Brazil (including EAD) in the light of theoretical directory (Foucault, 2013). With this research we intend to help the academy fill the gaps regarding to the data‟s source about this subject. To achieve the objectives, we used as methodological approach, the documentar research which is linked to the qualitative research, its object is to study by the oficial documents the federal, state and municipal spheres. For the theoretical support we use Foucault (2013); Benthan (2000) and Maeyer (2006). The analyzed data refer to the years 2013 and 2014. By these analysis available on the website of the Ministry of Justice, it was possible to establish some relationships between the total number of prisioners and the number of prisioners in educational activity.